The Mediation Role of Productivity in the Effect of Islamic Corporate Governance on Islamic Corporate Social Responsibility Disclosure - Ichsan Setiyo Budi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2021)
Research aims: This study aims to examine the indirect effect of Islamic Corporate Governance (ICG) on Islamic Corporate Social Responsibility Disclosure (ICSR) with productivity as mediation.Design/Methodology/Approach: This study used secondary data sourced from annual reports, corporate governance reports, and financial reports of Islamic banking in Indonesia for the period 2008 to 2019, with the criteria of Islamic banks (IBs) that have not been established for 12 years, and observations carried out since they were established until 2019. The sampling technique was done by convenience sampling and obtained 121 observations, and research testing employed regression analysis.Research findings: The results found that banking productivity fully mediated Islamic corporate governance's effect on Islamic Corporate Social Responsibility Disclosure. Thus, good productivity is an absolute requirement that must be fulfilled to carry out a good social function, as reflected in the Islamic Corporate Social Responsibility disclosure.Theoretical contribution/Originality: This study reaffirms and develops a new model of the relationship between ICG and ICSR disclosure in IBs.Practitioner/Policy implications: This research was conducted based on stakeholder theory, which is later developed into stakeholder theory from an Islamic perspective.Research limitation/Implication: First, this study used the ICG variable and the ICSR disclosure, but the researcher did not discuss the quality of disclosure. Second, this study did not test the reliability of the ICSR disclosure.